Screening for anaplastic lymphoma kinase (ALK) gene rearrangements in non‐small‐cell lung cancer in New Zealand. Issue 6 (14th June 2020) - McKeage, Mark J.; Tin Tin, Sandar; Khwaounjoo, Prashannata; Sheath, Karen; Dixon‐McIver, Amanda; Ng, Daniel; Sullivan, Richard; Cameron, Laird; Shepherd, Philip; Laking, George R.; Kingston, Nicola; Strauss, Magreet; et al.
Abstract: Background: Lung cancer is a major cause of death in New Zealand. In recent years, targeted therapies have improved outcomes. Aim: To determine the uptake of anaplastic lymphoma kinase (ALK) testing, and the prevalence, demographic profile and outcomes of ALK‐positive non‐small‐cell lung cancer (NSCLC), in New Zealand, where no national ALK‐testing guidelines or subsidised ALK tyrosine kinase inhibitor (TKI) therapies are available. Methods: A population‐based observational study reviewed databases to identify patients presenting with non‐squamous NSCLC over 6.5 years in northern New Zealand. We report the proportion tested for ALK gene rearrangements and the results. NSCLC samples tested by fluorescence in situ hybridisation were retested by next generation sequencing and ALK immunohistochemistry. A survival analysis compared ALK‐positive patients treated or not treated with ALK TKI therapy. Results: From a total of 3130 patients diagnosed with non‐squamous NSCLC, 407 (13%) were tested for ALK gene rearrangements, and patient selection was variable and inequitable. Among those tested, 34 (8.4%) had ALK‐positive NSCLC. ALK‐positive disease was more prevalent in younger versus older patients, non‐smokers versus smokers and in Māori, Pacific or Asian ethnic groups than in New Zealand Europeans. Fluorescence in situ hybridisation, ALK immunohistochemistry and next generation sequencing showed broad concordance for detecting ALK –positive disease under local testing conditions. Among patients with ALK‐positive metastatic NSCLC, those treated with ALK TKI survived markedly longer than those not treated with ALK TKI (median overall survival 5.12 vs 0.55 years). Conclusion: Lung cancer outcomes in New Zealand may be improved by providing national guidelines and funding policy for ALK testing and access to subsidised ALK TKI therapy.